ECO-CDA AND COUNTER-DISCOURSE: FROM EXOTIC LUXURY TO NONHUMAN ANIMAL EXPLOITATION IN CIVET COFFEE - Gavilan Tatin, Ingrid A. (Sanata Dharma University, 2024)
Civet coffee, an exotic beverage produced through the unique involvement of the Asian palm civet, has garnered attention and controversy. The study emphasizes the importance of amplifying marginalized voices and advocating for animal liberation and ecological perspectives through counter-discourse. Specifically, the research aims to analyze the counter-discourse arising from a webpage that describes a tourist's visit to a civet coffee plantation. This article employs Eco-CDA, a framework grounded in Critical Discourse Analysis and ecolinguistics, to critically analyze the discourse surrounding civet coffee production. Through discourse and semantic analysis, the study exposes the failure of the prevailing discourse to address ethical concerns and promote sustainable practices. In conclusion, this research aims to contribute to the transformation of societal norms by advocating for the recognition of animal rights. It calls for a comprehensive reevaluation of coffee production practices, emphasizing the need for ethical considerations in animal treatment.